Measuring IgA Anti-[beta]2-Glycoprotein I and IgG/IgA Anti-Domain I Antibodies Adds Value to Current Serological Assays for the Antiphospholipid Syndrome - Pericleous, Charis; Ferreira, Isabel; Borghi, Orietta; Pregnolato, Francesca; McDonnell, Thomas; Garza-Garcia, Acely; Driscoll, Paul; Pierangeli, Silvia; Isenberg, David; Ioannou, Yiannis; Giles, Ian; Meroni, Pier Luigi; et al. (PloS one, 2016)
Currently available clinical assays to detect antiphospholipid antibodies (aPL) test for IgG and IgM antibodies to cardiolipin (aCL) and [beta].sub.2 -glycoprotein I (a[beta].sub.2 GPI). It has been suggested that testing for IgA aPL and for antibodies to Domain I (DI), which carries the key antigenic epitopes of [beta].sub.2 GPI, could add value to these current tests. We performed an observational, multicenter cohort study to evaluate the utility of IgG, IgM and IgA assays to each of CL, [beta].sub.2 GPI and DI in APS. Serum from 230 patients with APS (n = 111), SLE but not APS (n = 119), and 200 healthy controls were tested for IgG, IgM and IgA aCL, a[beta].sub.2 GPI and aDI activity. Patients with APS were further classified into thrombotic or obstetric APS. Logistic regression and receiver operator characteristic analyses were employed to compare results from the nine different assays. All assays displayed good specificity for APS; IgG aCL and IgG a[beta].sub.2 GPI assays however, had the highest sensitivity. Testing positive for IgA a[beta].sub.2 GPI resulted in a higher hazard ratio for APS compared to IgM a[beta].sub.2 GPI. Positive IgG, IgM or IgA aDI were all associated with APS, and in subjects positive for aCL and/or a[beta].sub.2 GPI, the presence of aDI raised the hazard ratio for APS by 3-5 fold. IgG aCL, a[beta].sub.2 GPI, aDI and IgA aDI were associated with thrombotic but not obstetric complications in patients with APS. Measuring IgG aDI and IgA a[beta].sub.2 GPI and aDI may be useful in the management of patients with APS, particularly thrombotic APS.